Moving the Needle Toward Fair Compensation in Pediatric Nephrology - Weidemann, Darcy K.; Ashoor, I. A.; Soranno, D. E.; Sheth, R.; Carter, C.; Brophy, P. D. (Frontiers in Pediatrics, 2022)
Remuneration issues are a substantial threat to the long-term stability of the pediatric nephrology workforce. In contrast to adult nephrology, the majority of pediatric nephrologists practice in an academic setting affiliated with a university and/or children’s hospital. The pediatric nephrology service line is crucial to maintaining the financial health and wellness of a comprehensive children’s hospital. However, in the current fee-for-service system, the clinical care for children with kidney disease is neither sufficiently valued, nor appropriately compensated due to the structural biases inherent in the current payment system. Compensation models for pediatric subspecialists are derived from the relative value unit (RVU) system which characterize clinical productivity by work volume, thereby assigning relative value components to specific work identified in the Current Procedural Terminology code. RVUs are now the predominant currency for clinical productivity and are benchmarked nationally, and subsequently used for physician contracts. Such salary offers are often obscure and favor the negotiation powers of the hospital over the individual. An individual may very well accept a salary offer below fair market value due to ignorance or lack of perceived powers of negotiation. This cycle is perpetuated in the data used for subsequent survey cycles and benchmarks. The perceived negative financial compensation is a significant driver of waning trainee interest in the field which is one of the least attractive specialties for students, with a significant proportion of training spots going unfilled each year and one of the most stagnant growth rates of all of the pediatric subspecialties. It is uncertain whether the pediatric nephrology workforce will meet the growing needs of children with kidney disease without a substantial overhaul of the current reimbursement policies. This article reviews the current state of financial compensation issues plaguing the pediatric nephrology subspecialty. We further outline strategies for pediatric nephrologists, hospital administrators, and policy-makers to improve the landscape of financial reimbursement to pediatric subspecialists. The ideal state is to create fair physician compensation plans which align clinical activity with mutually-agreed upon, outcomes-based, transparent, and meaningful metrics for current non-RVU producing activities that harmonize with hospital and personal mission statements.